Dementia, Preclinical Studies in Neurodegeneration and its Potential for Translational Medicine in South America (2016)
ABSTRACT: Latin-American people with dementia will increase to an astounding 368% in 2050, higher than USA and Europe. In addition, to sporadic dementia type like Alzheimer, and vascular dementia (VaD) progression after Cerebrovascular disease is also found. These incidences are increased in Colombia by specific populations affected with pure Neurodegenerative and VaDs like Autosomical Dominant familial Alzheimer’s disease (AD) and Cerebral Autosomal-Dominant Arteriopathy with Subcortical Infarcts and Leukoencephalopathy (CADASIL). In spite of the enormous human effort with and economical effort and investment costs, neither sporadic nor genetic kinds of dementia progression have been prevented or blocked yet. Currently, there exist several animal models that partially solve the understanding of the neurodegenerative etiopathogenesis and its treatment. However, when the potential therapies are translated to humans, those do not work or present a limited action. Main difficulties are the diverse comorbility associated to the cause and/or several affected brain regions, reducing the efficacy of some therapies which are limited to a tissue-specific action or modulating a kind of neurotransmission. Global investigation suggests that a general prevention could be achieved with the improvement in the quality of lifestyle, including healthy diet, physical and mental activity, and avoiding mechanical or chemical pro-inflammatory events in an early stage in the most of non-communicable diseases. In this review article, we present some molecular targets and preclinical studies in animal models to propose strategies that could be useful in a future translation to prevent or block neurodegeneration: one is gene therapy; silencing pathogenic genes in critical brain areas where excitotoxicity arise and spread. Another is to take advantage of the natural source and its wide biodiversity of natural products that are capable of identifying, by the blocking and prevention of neurodegeneration. On the other side, the casuistic of pure dementias in the Latin-American region gives an exceptional opportunity to understand the pathogenesis in these human populations. Further, this is in support of the basic and clinical researchers working on an interaction for a better understanding and medical care of mixed dementias, which have more complex factors than pure ones. However, to promote the translation of any therapeutical alternative is necessary to clarify the normative and the protocols for developing clinical trials with original candidates or work upon strategies proposed from South-American countries.